Age as a predictor of additional surgeries following initial closed reduction for children with developmental dysplasia of the hip: the 10-year experience of a national paediatric orthopaedic unit. Issue 3 (May 2023) - Hurley, Robert J; Davey, Martin S; Davey, Matthew G; Groarke, Patrick; Kennedy, Jim; Moore, David P
Background and purpose: Dislocated and unstable hip joints which do not stabilize in an orthosis in the neonatal period require operative intervention to achieve a stable concentric joint. The aim of this study is to assess the requirement for further operative intervention in patients who have undergone successful closed reduction to treat developmental dysplasia of the hip (DDH). Methods: We identified all patients who had undergone closed reduction of an unstable hip joint at our institution within 10 years, with further identification of patients who underwent a second procedure. We used logistic regression to evaluate correlation between age at closed reduction and the probability of secondary procedures. Results: A total of 694 patients (84.5% females) who underwent a closed reduction in the study period were identified. 235 were excluded (patients with underlying genetic conditions, neuromuscular disorders, syndromic disorders). 250 patients had closed reductions only. 209 patients (45.5%) had at least 1 secondary procedure after their initial closed reduction. In multivariable analysis, female gender (OR 0.310; 95% CI, 0.108–0.885; p = 0.029) and patients aged ⩽12 months at the time of first surgery (OR 0.055; 95% CI, 0.007–0.423; p = 0.005) independently predicted being less likely to require a second surgery for their DDH. Discussion: In conclusion, we found that a significant proportion of children (45.5%) who underwent closed reduction of a dislocated hip required additional surgical intervention in early childhood. Our data show that those children who undergo later closed reduction of a dislocated hip in DDH after 12 months of age, and male infants, have a significantly higher incidence of additional surgical intervention.